APPLICATION OF TAEKWONDO PARALYMPIC RULES FOR SPARRING COMPETITION IN TERMS OF SPECIAL NEEDS PHYSICAL EDUCATION FOR REDUCTION OF CHALLENGING BEHAVIOUR - Mosler, Dariusz (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Aim of the study: Para Taekwondo is divided into competition of sparring (kyorugi) and patterns of defense-and-attack motions (poomse). The first one is limited to orthopedic-like disabilities, while the other also include intellectual and visual impairments. The aim of this study is to analyze rules of sparring competitions to propose a pattern of sparring-like exercises for people with intellectual disability for the purpose of reducing aggressive like behaviors that often occurs in this group. Methods: Analysis of the competition rules were compared with existing intervention and knowledge about reducing aggressive behaviors in a group of intellectually disabled people. Results: Limited area of striking, which exclude head and punishment for disobeying rules serve as similar intervention as in behavioral therapy for reducing aggressiveness. Conclusions: Limiting striking zone during practice may induce subconscious restriction in aggressive behavior, improving social adjustment for people with intellectual disability.